Advancements in Gel Polymer Electrolytes: From Structural Engineering to Functional Applications - Hou, Kaichuan (Exploring Science Academic Conference Series, 2026)
Gel polymer electrolytes (GPEs) have emerged as a promising class of quasi -solid-state electrolytes that combine the liquid -like interfacial compatibility of conventional liquid electrolytes with the mechanical integrity and leakage resistance of solid -state systems. Despite these advantages, their deployment in high - energy-density lithium batteries is still constrained by insufficient room -temperature ionic conductivity, low lithium-ion transference number (t Li+), limited mechanical robustness, and unstable electrode/electrolyte interfaces. This review provides a mechanism -guided overview of recent advances in GPEs, with particular emphasis on the coupled regulation of ionic conductivity and t Li+. First, the compositional features, ion - transport mechanisms, and key electrochemical evaluation metrics of GPEs are summarized to establish a unified structure -property framework. Subsequently, three major modification strategies are critically discussed: polymer -matrix engineering for crystallinity suppression and pathway construction, single -ion- conducting and anion -regulating designs for enhancing t Li+, and functional filler incorporation for simultaneously improving mechanical strength, interfacial stability, and ion transport. Representative examples based on cross -linked networks, high -entropy gel systems, porous/aligned polymer frameworks, anion-anchored polymer electrolytes, boron -based anion receptors, inorganic nanofillers, metal -organic frameworks, and covalent organic frameworks are discussed in relation to their underlying mechanisms. Finally, the application prospects of GPEs in high -energy lithium batteries, flexible/wearable devices, and intelligent energy-storage systems are analyzed. Future research directions, including data -driven electrolyte design, scalable in situ manufacturing, and multifunctional integration, are proposed to guide the development of next-generation high-performance GPEs.